2015
DOI: 10.1128/aem.01287-15
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli Cells in Aqueous Solution by Atmospheric-Pressure N 2 , He, Air, and O 2 Microplasmas

Abstract: bAtmospheric-pressure N 2 , He, air, and O 2 microplasma arrays have been used to inactivate Escherichia coli cells suspended in aqueous solution. Measurements show that the efficiency of inactivation of E. coli cells is strongly dependent on the feed gases used, the plasma treatment time, and the discharge power. Compared to atmospheric-pressure N 2 and He microplasma arrays, air and O 2 microplasma arrays may be utilized to more efficiently kill E. coli cells in aqueous solution. The efficiencies of inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…In all systems tested, a strong positive correlation between the sterilization efficiency and the ROS concentration was demonstrated, suggesting a possible avenue for process optimization, for instance, through fast and efficient transport of plasma-generated species to the target organisms23537. Generally, cell membranes containing unsaturated fatty acids and protein molecules can sustain significant damage from the strong oxidizing effects of ROS6, interfering with the ability of the cell membrane to effectively transport ions and polar compounds.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In all systems tested, a strong positive correlation between the sterilization efficiency and the ROS concentration was demonstrated, suggesting a possible avenue for process optimization, for instance, through fast and efficient transport of plasma-generated species to the target organisms23537. Generally, cell membranes containing unsaturated fatty acids and protein molecules can sustain significant damage from the strong oxidizing effects of ROS6, interfering with the ability of the cell membrane to effectively transport ions and polar compounds.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is difficult for these highly reactive radicals to penetrate the gas−liquid interface (several ÎŒm to hundreds of ÎŒm) or diffuse into the solution within their short lifetime during plasma treatment3334. As for H 2 O 2 and O 3 , they both have the same bacterial inactivation mechanism, reacting with H 2 O molecules to form OH radicals (O 3  + H 2 O → 2OH + O 2 and ), although the oxidation-reduction potential of H 2 O 2 (acid, 1.776 V) is much lower than the corresponding value for O 3 (2.07 V)3536. By generating species in the close proximity to the intended microbial targets, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…formation processes are as follows. (1) H formation: the reaction between electrons and O 2 is e + O 2 → e + O( 3 P) + O( 1 D), followed by O( 1 D) + H 2 O → 2OH . The OH is in X 2 ∏ 2/3 state .…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, we found that the environmental humidity (i.e., H 2 O content in the atmosphere) greatly affects the plume length of plasma. The decrease of plasma electrons through absorption by water molecules in ambient air decreases the ionization of atoms and molecules by electron effect . During air discharge, the change in plume length of plasma influences the content of reactive oxygen species (ROS) introduced in the solution, resulting in uncertainties in the product content.…”
Section: Introductionmentioning
confidence: 99%
“…2B). Various ROS and RNS are present in aqueous solutions treated with NTAP [29]; therefore, the detection of 1 O 2 in the experimental solution suggests that 1 O 2 might have diffused into the solution after being generated by the NTAAP device. The air pressure at the surface of a solution differs according to treatment distance, and this may be attributed to the inverse distancedependent increase of 1 O 2 .…”
Section: Discussionmentioning
confidence: 99%